Effect of tool pin shapes on microstructure and mechanical behaviour of friction stir welding of dissimilar aluminium alloys. (2023) - Balamurugan, S.; Jayakumar, K.; Anbarasan, B.; Rajesh, M.
Abstract: The mechanical and microstructure characterizations of friction stir welding (FSW) joints of 5052-H32 with 6061-T6 aluminium alloys (AA) were investigated in this research. With two distinct tools (Taper cylinder and Threaded cylinder), the microstructural change associated to the mechanical characteristics of an FSW of dissimilar AA has been investigated under constant welding conditions such as welding speed (WS) and tool rotation speed (TRS) are 60 mm/min and 900 rpm respectively. For instance, in the hardness profile, the lesser values were obtained in the AA6061 alloy. The maximum and minimum weld joint strength were approximately 165.84 MPa and 133.85 MPa from the FSW, showed lower strength than the base material. The highest joint Efficiency of the dissimilar weld was 78.37 %, and the maximum hardness is 71 HV obtained. The defect-free stir zone development and grain size strengthening were credited with it as well. The elongations of the welded joints were measured to be 11.6 % and 7.2 %. It was discovered that using a tool with a taper pin profile and a threaded pin profile produced a joint with better tensile strength, a larger nugget area, and a smoother surface finish. Finally, it was discovered that a fine grain microstructure created by using a taper pin profile resulted in stronger welded connections compared with threaded pin profile.